Mud crab reovirus hijacks the lipogenesis-lipophagy pathway to fuel viral replication via metabolic reprogramming - Xiaoyu Wang; Jing Peng; Yuanze Xu; Liangyu Chen; Ngoc Tuan Tran; Xianliang Zhao; Yueling Zhang; Zhixun Guo; Shengkang Li (Aquaculture, 2026)

Lipid-lowering activity of Gracilaria lemaneiformis polysaccharide in the liver of rabbitfish (Siganus canaliculatus) - Md. Akibul Hasan Bakky; Jinxian Liang; Ngoc Tuan Tran; Akram Ismael Shehata; Vicent Michael Shija; Jinkun Li; Taoqiu Deng; Zhenya Du; Ming Zhang; Yueling Zhang; Shengkang Li (Aquaculture, 2026)

Polysaccharide‐Induced Immunoregulation, Signaling Pathways, and Stress Mitigation in Aquaculture Animals: A Review - Md. Akibul Hasan Bakky; Peijun Yi; Ngoc Tuan Tran; Qian Sun; Ming Zhang; Yueling Zhang; Shengkang Li (Reviews in Aquaculture, 2025)
Aquaculture, encompassing the cultivation of diverse saltwater and freshwater fish and shellfish species, is rapidly expanding, driven by the pressing need for sustainable food production. However, intensified farming practices often lead to significant economic losses due to fish mortality from infectious diseases and stress‐related conditions. Consequently, enhancing the immune responses of farmed species has become vital for sustainable management. This has encouraged a growing interest in natural and eco‐friendly bioactive compounds as alternatives to synthetic chemicals for disease prevention. Among these, polysaccharides from various natural sources have emerged as promising candidates, administered through dietary inclusion, intraperitoneal injection, or immersion. As prebiotics, these polysaccharides enhance the immunity and overall health of aquaculture species by modulating both innate and adaptive immune responses, including lysozyme activity, phagocytosis, and cytokine production. This review critically examines the latest advances in polysaccharide‐induced immunoregulation, highlighting their influence on key signaling pathways, which play pivotal roles in immune modulation. Additionally, the potential of polysaccharides to mitigate stress caused by environmental factors is discussed, demonstrating their ability to enhance growth performance and disease resistance. The collective findings underscore the value of polysaccharides as sustainable alternatives to antibiotics, aligning with the increasing consumer demand for antibiotic‐free aquaculture products and supporting the advancement of global aquaculture sustainability.

Cover Image - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
The cover image is based on the Review Article Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota by Qingshuang Zhang and Hongwei Yang et al., https://doi.org/10.1111/raq.12852 . [Correction added on 27 March 2024, after first online publication: Cover image has been changed] image

Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
Immunostimulants were widely used in aquafeed due to their multiple important functions, including promoting growth, enhancing non‐specific defence mechanisms and resisting infectious diseases. But the efficiencies of the positive effects of immunostimulants were affected by the duration of the administration and their dose. Short‐term and normal‐dose of immunostimulants promoted the growth and enhance non‐specific immunity of aquatic animals. However, improper use led to several immune disorders, including immune tolerance, immune exhaustion and over‐immunity. The application of two immunostimulant diets in rotation technique and the intermittent use of immune stimulant diets may solve the problems associated with immune disorders, but this application method will be limited by both species and immunostimulants. The occurrence of immune disorders is accompanied by different degrees of gut microbiota dysbiosis, especially significantly up‐regulated the abundance of Proteobacteria. Besides, the gut symbiotic microbiota plays a significant role in host immunity. Consequently, the regulation of gut microbiota may be an effective way to modulate immune disorders caused by improper use of polysaccharide immunostimulants. Regulating the gut microbiota not only solves the negative effects caused by improper use of immunostimulants without restrictions on both species and immunostimulants, but also has the advantage of simplicity and convenience compared to conventional approaches. In summary, this article reviews the possible negative effects caused by improper use of immunostimulants on aquatic animals and compares regular approaches with regulating gut microbiota. And gut microbiota maybe be used as a therapeutic target to improve immune disorders caused by immunostimulants in aquatic animals.

Metabolic reprogramming in crustaceans: A vital immune and environmental response strategy - Zhongyan Wang; Yueling Zhang; Defu Yao; Yongzhen Zhao; Ngoc Tuan Tran; Shengkang Li; Hongyu Ma; Jude Juventus Aweya (Reviews in Aquaculture, 2022)
Most host organisms undergo metabolic changes in response to pathogens, environmental cues or simply to boost their immunity. Metabolic modulation has therefore been exploited by both host and pathogens to outwit the other during host–pathogen interactions. Recent studies have revealed that a growing number of metabolites and metabolic processes in crustaceans are crucial in host–pathogen interactions. Here, we reviewed recent work on metabolic changes during immune response of crustaceans and the metabolic reprogramming that takes place in the host induced by pathogens, environmental cues or as a host strategy to withstand these changes or clear the pathogen. In aquaculture crustaceans, limited studies exist on this subject; hence, we will also highlight themes for possible future research on metabolite reprogramming and how this strategy can be leveraged to improve sustainable aquaculture and enhance crustaceans’ response to pathogens and environmental changes.

Clostridium butyricum : a promising probiotic confers positive health benefits in aquatic animals - Ngoc Tuan Tran; Zhongzhen Li; Hongyu Ma; Yueling Zhang; Huaiping Zheng; Yi Gong; Shengkang Li (Reviews in Aquaculture, 2020)
Clostridium butyricum is a bacterium of rod shape, strictly anaerobic, Gram‐positive and form spores. Short‐chain fatty acids, biofuel compounds and precursors of biomaterials (H 2 , butanol and 1,3‐propanediol) are produced by C. butyricum during the fermentation of carbohydrates and sugars. In humans and animals, although C. butyricum has been found to be associated with botulism in infant and necrotising enterocolitis in preterm neonates, some strains have been demonstrated to be beneficial as probiotics. In aquatic animals, the application of C. butyricum as a probiotic has been commonly considered. In this review, we described and documented what we knew about the isolation, identification, phenotypic and biochemical characteristics, safety, pathogenicity and the mechanisms of action of C. butyricum in the gastrointestinal tract of aquatic animals. The evidence on the roles that C. butyricum plays in improving growth performance, digestibility, survival rate, immune response, disease resistance and the structure of intestinal tract, as well as the modulation of gut commensal microbiota and metabolic disorders in aquatic animals, is summarised. Albeit the probiotic C. butyricum has been applied in aquaculture, and further research, such as the inter‐relationships between the probiotic and the immune system of the host and the possible application of C. butyricum as an alternative to antibiotic substitution for the prevention and treatment of diseases, is required for future detailed studies.

Effects of ammonia on shrimp physiology and immunity: a review - Mingming Zhao; Defu Yao; Shengkang Li; Yueling Zhang; Jude Juventus Aweya (Reviews in Aquaculture, 2020)
The rapid expansion in shrimp farming comes with problems such as inadequate culture technology, disease outbreak, water pollution and other environmental degradation‐related problems. Prominent among these is the level of ammonia, which has been rising steadily in the last couple of years, mainly due to farming practices and other anthropogenic activities, and therefore has had consequent effects on marine life, especially shrimp. While optimal ammonia levels are a good source of nitrogen for marine phytoplankton that increases the level of dissolved oxygen in water as well serves as food for shrimp, high levels of ammonia are harmful to shrimp. When shrimp pond ammonia levels go beyond the tolerance limits, it inhibits chitinase expression, moulting, growth, phenoloxidase and haemolymph antimicrobial activity, thereby attenuating shrimp innate immune response. In this review, we bring together recent information on the effects of ammonia stress on the growth, physiology, biochemistry, ammonia‐metabolizing enzymes and immunity of shrimp. We also propose areas of research that can be explored in the breeding of new ammonia‐tolerant and disease‐resistant shrimp with robust immune and/or physiological systems that could withstand environmental stress and pathogens.

Progress and perspectives of short‐chain fatty acids in aquaculture - Ngoc Tuan Tran; Zhongzhen Li; Shuqi Wang; Huaiping Zheng; Jude Juventus Aweya; Xiaobo Wen; Shengkang Li (Reviews in Aquaculture, 2020)
Gut microbiota is important and plays a crucial role in the host health and nutritional metabolism through multiple mechanisms. Short‐chain fatty acids (SCFAs), which are carboxylic acids with aliphatic tails